Avoiding Radical Surgery Improves Early Survival in Elderly Patients With Rectal Cancer, Demonstrating Complete Clinical Response After Neoadjuvant Therapy: Results of a Decision-Analytic Model. Issue 2 (February 2015) - Smith, Fraser McLean; Rao, Christopher; Perez, Rodrigo Oliva; Bujko, Krzysztof; Athanasiou, Thanos; Habr-Gama, Angelita; Faiz, Omar
Abstract : BACKGROUND: In elderly and comorbid patients with rectal cancer, radical surgery is associated with significant perioperative mortality. Data suggest that a watch-and-wait approach where a complete clinical response is obtained after neoadjuvant chemoradiotherapy might be oncologically safe. OBJECTIVE: This study aimed to determine whether patient age and comorbidity should influence surgeon and patient decision making where a complete clinical response is obtained. DESIGN: Decision-analytic modeling consisting of a decision tree and Markov chain simulation was used. Modeled outcome parameters were elicited both from comprehensive literature review and from a national patient outcomes database. SETTINGS: Outcomes for 3 patient cohorts treated with neoadjuvant therapy were modeled after either surgery or watch and wait. PATIENTS: Patients included 60-year-old and 80-year-old men with mild comorbidities (Charlson score <3) and 80-year-old men with significant comorbidities (Charlson score >3). MAIN OUTCOME MEASURES: Absolute survival, disease-free survival, and quality-adjusted life years were measured. RESULTS: The model found that absolute survival was similar in 60-year-old patients but was significantly improved in fit and comorbid 80-year-old patients at 1 year after treatment where watch and wait was implemented instead of radical surgery, with a survival advantage of 10.1% (95% CI, 7.9–12.6) and 13.5% (95% CI, 10.2–16.9). At all of the other time points, absolute survival was equivalent for both techniques. There were no short- or long-term differences among any patient groups managed either by radical surgery or watch and wait in terms of either disease-free survival or quality-adjusted life years. LIMITATIONS: Oncologic data for the watch-and-wait approach used for this study is derived from only a small number of studies pertaining to a highly selected group of patients. The 90-day postoperative mortality rate derived from the United Kingdom population-based study might be lower in other countries or individual institutions. CONCLUSIONS: This study suggests competing effects of oncologic and surgical risk when using watch-and-wait management and that elderly and comorbid patients have the most to gain from this approach.